Integrating Islamic Values into EFL Instruction: A Thematic Framework for Culturally Responsive Pedagogy - Athaya Dwi Insyra; Amanda Azzahra; Esliana; Fathir Nur Rahman; Kalayo Hasibuan (Journal of Applied Linguistics, 2026)
This study explores the integration of Islamic values into English as a Foreign Language (EFL) teaching, particularly in Muslim-majority educational contexts. As language and culture are closely interconnected, EFL instruction that neglects learners’ cultural and religious backgrounds may result in reduced engagement, moral conflict, and ineffective learning outcomes. Many widely used EFL materials are developed in Western contexts and often contain content that contradicts Islamic norms, such as references to alcohol, dating, or gambling. This creates a need for culturally responsive teaching practices that respect Islamic teachings while maintaining language learning objectives. Using a qualitative approach, this study involved structured group discussions with five undergraduate EFL students and a comprehensive literature review of academic sources and Islamic texts. Thematic analysis revealed three key areas central to effective Islamic-based EFL instruction: cultural awareness, material appropriateness, and ethical communication. Cultural awareness helps teachers foster inclusive environments and build stronger relationships with students. Culturally appropriate materials ensure learners can engage with content without compromising their values. Meanwhile, Islamic communication principles emphasize respectful and purposeful language use, aligning with Qur’anic and prophetic teachings. The findings suggest that integrating Islamic perspectives into EFL education not only supports language acquisition but also promotes students’ moral and spiritual development. This study contributes to the discourse on culturally responsive pedagogy by emphasizing the need to localize curriculum content and train educators in culturally and religiously aligned instructional strategies. As global interest in culturally sensitive education grows, this research underscores the importance of aligning language teaching with learners’ cultural and ethical frameworks to ensure holistic educational success. Keywords : Islamic values; EFL teaching; cultural awareness; culturally responsive pedagogy